2006
DOI: 10.1111/j.1747-5457.2006.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Potential, Thermal Maturity and the Oil Window of Oil Shales and Coals in Cenozoic Rift Basins, Central and Northern Thailand

Abstract: Oil shales and coals occur in Cenozoic rift basins in central and northern Thailand. Thermally immature outcrops of these rocks may constitute analogues for source rocks which have generated oil in several of these rift basins. A total of 56 oil shale and coal samples were collected from eight different basins and analysed in detail in this study. The samples were analysed for their content of total organic carbon (TOC) and elemental composition. Source rock quality was determined by Rock‐Eval pyrolysis. Refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…Kalkreuth (1982) also found that the vitrinite reflectance in British Colombian coals gradually decreased with increases in liptinite content, and suggested that the effect was caused by diffusion of bituminous substances from the liptinite macerals into the surrounding vitrinite. Gentzis and Goodarzi (1994) and Petersen et al (2006) have similarly noted suppression of vitrinite reflectance in coals and other sediments, including oil shales, associated with a high proportion of liptinite macerals.…”
Section: Organic Petrologymentioning
confidence: 80%
“…Kalkreuth (1982) also found that the vitrinite reflectance in British Colombian coals gradually decreased with increases in liptinite content, and suggested that the effect was caused by diffusion of bituminous substances from the liptinite macerals into the surrounding vitrinite. Gentzis and Goodarzi (1994) and Petersen et al (2006) have similarly noted suppression of vitrinite reflectance in coals and other sediments, including oil shales, associated with a high proportion of liptinite macerals.…”
Section: Organic Petrologymentioning
confidence: 80%
“…As discussed in Section 3, vitrinite in such alginite-bearing rocks commonly yields suppressed VR values (Hutton and Cook, 1980;Price and Barker, 1985;Lo, 1993;Petersen et al, 2006). Although considerable VR suppression applies to only one sample from the lacustrine mudstones, using this measured VR value would underestimate the thermal maturity of the Upper Oligocene source rocks.…”
Section: Thermal Maturity Gradientmentioning
confidence: 93%
“…VR suppression is caused by incorporation of extra hydrogen into the vitrinite leading to perhydrous compositions, and in liptinite-rich coals and shales a possible mechanism can be bitumen impregnation (Hao and Chen, 1992;Petersen and Rosenberg, 1998;Petersen and Vosgerau, 1999). VR suppression may be particularly pronounced in alginite-rich shales (such as some oil shales and marine black shales), where it may be 0.5%R o or more (Hutton and Cook, 1980;Price and Barker, 1985;Lo, 1993;Petersen et al, 2006). VR suppression commonly causes considerable problems in deriving accurate VR values for source rock sections.…”
Section: Problems With Thermal Maturity Determination From Dommentioning
confidence: 98%
See 1 more Smart Citation
“…The VR-T peak relationship was used by Petersen et al (2006) to calculate the geothermal gradient for the Suphan Buri Basin, central Thailand. As shown below, this method contrasts with the kinetic EASY%R o model, which allows time to influence VR during the entire burial history (Burnham and Sweeney, 1989;Sweeney and Burnham, 1990).…”
Section: Introductionmentioning
confidence: 99%